Motivation of medical students: selection by motivation or motivation by selection. Issue 1 (December 2016) - Wouters, Anouk; Croiset, Gerda; Galindo-Garre, Francisca; Kusurkar, Rashmi
Abstract Background Medical schools try to implement selection procedures that will allow them to select the most motivated students for their programs. Though there is a general feeling that selection stimulates student motivation, conclusive evidence for this is lacking. The current study aims to use the perspective of Self-determination Theory (SDT) of motivation as a lens to examine how medical students' motivation differs in relation to different selection procedures. The hypotheses were that 1) selected students report higher strength and autonomous motivation than non-selected students, and 2) recently selected students report higher strength and autonomous motivation than non-selected students and students who were selected longer ago. Methods First- (Y1) and fourth-year (Y4) medical students in the six-year regular programme and first-year students in the four-year graduate entry programme (GE) completed questionnaires measuring motivation strength and type (autonomous-AM, controlled-CM). Scores were compared between students admitted based on selection, lottery or top pre-university GPA (top GPA) using ANCOVAs. Selected students' answers on open-ended questions were analysed using inductive thematic analysis to identify reasons for changes in motivation. Results The response rate was 61.4 % (n = 357). Selected students (Y1, Y4 and GE) reported a significantly higher strength of motivation than non-selected students (Y1 and Y4 lottery and top GPA) (p < 0.01). Recently selected students (Y1 and GE) reported significantly higher strength (p < 0.01) and higher AM (p < 0.01) and CM (p < 0.05) than non-selected students (lottery and top GPA) and Y4 students who were selected three years ago. Students described that being selected enhanced their motivation as they felt autonomous, competent and that they belonged to a special group. These reported reasons are in alignment with the basic psychological needs described by Self-Determination Theory as important in enhancing autonomous motivation. Conclusions A comprehensive selection procedure, compared to less demanding admission procedures, does not seem to yield a student population which stands out in terms of autonomous motivation. The current findings indicate that selection might temporarily enhance students' motivation. The mechanism through which this occurs seems to be through feelings of autonomy, competence and relatedness inspired by selection.